Logical empiricism : historical & contemporary perspectives - Parrini, Paolo; Salmon, Wesley C.; Salmon, Merrilee H. (University of Pittsburgh Press Digital Editions, 2003)
This collection of essays reexamines the origins of logical empiricism and offers fresh insights into its relationship to contemporary philosophy of science.